Pregnancy after Succesful Fallopian Tube Recanalization - Trisha Alya Rahmi; Nur Fitri Fadila; Gunardi, Eka Rusdianto (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective: To report a pregnancy that ensued following the successful recanalization of a previously sterilized fallopian tube. The novel aspect of this report is its demonstration of a successful intrauterine pregnancy post-recanalization, despite a prior ectopic pregnancy resulting from tubal sterilization. Methods: Case report Case: A 35-year-old woman successfully conceived after the recanalization of a previously sterilized fallopian tube. It is noteworthy that she had previously experienced an ectopic pregnancy due to the tubal sterilization procedure. Conclusion: This case study highlights the potential for successful pregnancy following fallopian tube recanalization, even after an ectopic pregnancy caused by a prior sterilization procedure. This report underscores the complexity of reproductive outcomes in these scenarios. Keywords: fallopian tube recanalization, pregnancy, tube sterilization.